INVERSION IS A BRIDGE TO THE WONDERS OF THE LANGUAGE WORLD. - Tilavova, Malika (Журнал иностранных языков и лингвистики, 2021)
The role of foreign languages in our country, reforms after independence, the work done in the development of the industry on the basis of the Decree of the First President of December 10, 2012, testing the knowledge of our youth in IELTS, CEFR and other programs, available effective English language methods, inversion literature device and its place in literary works, its role in translation is reflected in this article.